Analisis Strategi Komunikasi Komunitas Yayasan Mentari Sehat Indonesia Mengenai Eliminasi TB di Kabupaten Klaten : Perspektif Teori Difusi Inovasi - Hadiba Qotrunnada; Sidiq Setyawan (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to determine the communication strategy used by the Mentari Sehat Indonesia Foundation (MSI) in Klaten Regency in its Tuberculosis (TB) elimination program. The background of this study is the high number of TB cases in Klaten Regency, thus emphasizing the importance of communication in disseminating health information, especially regarding Tuberculosis, to the public. This study uses a descriptive qualitative method using Everett M. Rogers' innovation diffusion theory. Data collection techniques include in-depth interviews and observations of cadres and counseling participants. The results of this study indicate that the main innovation used is counseling as a means of conveying information about TB. It has a relative advantage because it can provide knowledge and increase public awareness of TB. The communication channels used are interpersonal communication (face to face) and Instagram social media as a supporting medium. Obstacles experienced include the negative stigma in the community regarding TB. The role of agent of change and opinion leaders greatly influences the acceptance of innovations in the community. Based on the four elements of innovation diffusion consisting of innovation, communication channels, timeframe, and social systems, the communication strategy at the Mentari Sehat Indonesia Foundation (MSI) in Klaten Regency is considered effective in providing knowledge, forming positive attitudes and increasing public awareness of TB.